Prevalence and Clinical Management of Non-malarial Febrile Illnesses among Outpatients in the Era of Universal Malaria Testing in Malawi - Tembo, Atupele Kapito; Mathanga, Don; Bauleni, Andrew; Nyirenda, Osward; Pensulo, Paul; Ali, Doreen; Valim, Clarissa; Taylor, Terrie E.; Laufer, Miriam K. (The American Journal of Tropical Medicine and Hygiene, 2020)
Increasing access to rapid diagnostic tests for malaria (mRDTs) has raised awareness of the challenges healthcare workers face in managing non-malarial febrile illnesses (NMFIs). We examined NMFI prevalence, clinical diagnoses, and prescribing practices in outpatient clinics across different malaria transmission settings in Malawi. Standardized facility-based malaria surveillance was conducted at three facilities one of every 4 weeks over 2 years. Information on demographics, presenting symptoms, temperature, clinical diagnosis, and treatment were collected from outpatients presenting with malaria-like symptoms. Of the 25,486 patients with fever, 69% had NMFI. Non-malarial febrile illness prevalence was lower in 5- to 15-year-old patients (55%) than in children < 5 years (72%) and adults > 15 years of age (77%). The most common clinical diagnoses among febrile patients with negative mRDTs in all age-groups and settings were respiratory infections (46%), sepsis (29%), gastroenteritis (13%), musculoskeletal pain (9%), and malaria (5%). Antibiotic prescribing was high in all age-groups and settings. Trimethoprim–sulfamethoxazole (40%) and amoxicillin (29%) were the most commonly prescribed antibiotics and were used for nearly all clinical diagnoses. In these settings with minimal access to diagnostic tools, patients with fever and a negative mRDT received a limited number of clinical diagnoses. Many were likely to be inaccurate and were associated with the inappropriate use of the limited range of available antibiotics. Prescription and diagnostic practices for NMFIs in the facilities require research and policy input. Resource-limited malaria-endemic countries urgently need more point-of-care diagnostic tools and evidence-based diagnosis and treatment algorithms to provide effective and cost-efficient care.